Ответы и объяснения

Лучший Ответ!
2013-08-06T15:49:53+00:00
1)\ kx^2-6x+k=0\\ D=36-4k^2
Т.к. уравнение должно иметь 2 корня, то D>0
36-4k^2>0
k^2-9<0
k^2<9
-3<k<3\ => k=0;\ \pm1;\pm 2.
2) Используем знакомую формулу (a+b)^2=a^2+2ab+b^2
\begin{cases} (x+y)^2-2xy=40 \\ xy=-12 \end{cases} <=> \begin{cases} (x+y)^2+24=40 \\ xy=-12 \end{cases} <=>
\begin{cases} (x+y)^2=16 \\ xy=-12 \end{cases} <=> \begin{cases} x+y=\pm 4 \\ xy=-12 \end{cases} =>
\begin{cases} x+y=- 4 \\ xy=-12 \end{cases}\ u \lambda u\ \begin{cases} x+y=4 \\ xy=-12 \end{cases}
\begin{cases} x=-y- 4 \\ y(y+4)=12 \end{cases}\ u \lambda u\ \begin{cases} x=4-y \\ y(y-4)=12 \end{cases}
\begin{cases} x=-y- 4 \\ y^2+4y-12=0 \end{cases}\ u \lambda u\ \begin{cases} x=4-y \\ y^2-4y-12=0 \end{cases}
\begin{cases} y=2 \\ x=-6 \end{cases} u \lambda u\ \begin{cases} y=-6 \\ x=2 \end{cases} u \lambda u\ \begin{cases} y=6 \\ x=-2 \end{cases} u \lambda u\ \begin{cases} y=-2 \\ x=6 \end{cases}
Ответ: (-6; 2), (-2; 6), (2; -6), (6; -2).